29.3: High Resolution Flexible AMOLED with Integrated Gate‐Driver using Bulk‐Accumulation a‐IGZO TFTs. Issue 1 (June 2015) - Geng, Di; Kim, Hyo Min; Mativenga, Mallory; Chen, Yuan Feng; Jang, Jin
Abstract : We report the design and fabrication of a high resolution AMOLED with integrated gate driver using bulk‐accumulation amorphous‐indium‐gallium‐zinc‐oxide (a‐IGZO) thin‐film transistor (TFT) on a plastic substrate. The gate driver consisting 7 TFTs and 1 capacitor is small in physical size which is only 40 µm in width (pitch). At the supply voltage (VDD) of 20 V, the clock frequency of the gate driver approaches 250 kHz, corresponding to a pulse width of 2 µs. The gate driver could be operated under mechanical bending radius of 2mm, making it applicable to flexible high resolution active‐matrix displays. The demonstrated AMOLED on flexible substrate achieves good image quality with very high resolution.